Management of Crohn's disease and ulcerative colitis. Issue 8 (August 2017) - Ray, Christopher; Sagar, Peter
Abstract: Crohn's disease and ulcerative colitis (UC) are complex, contrasting disease processes that require multidisciplinary team management. The treatment modalities in inflammatory bowel disease are varied and the indications and threshold for surgery quite different in patients with UC compared with Crohn's disease. We discuss the panoply of surgical techniques available to the surgeon and IBD-patient whilst highlighting the potential sequelae, complimentary medical therapies, nutritional considerations and innovative techniques for reconstruction of the gastrointestinal tract.